Acute toxicity of organophosphate fenitrothion on biomarkers in prawn Palaemonetes argentinus (Crustacea: Palaemonidae) - Lavarias, Sabrina Maria Luisa (2015)
The effect of the organophosphate fenitrothion(FS) on the non-target freshwater prawn Palaemonetesargentinus was studied. Initially, the 96-h lethal concentration(LC50) of FS was determined in adult prawns.Inhibition of cholinesterase (ChE) in the muscle andhemolymph was assessed. Then, in the hepatopancreas,the activities of superoxide dismutase (SOD), catalase(CAT), and glutathione-S-transferase (GST) were analyzed.Lipid peroxidation (LPO) was also determined inthe hepatopancreas. The 96-h LC50 value was 1.12 μg/L.Hemolymph ChE activity showed a significant decreasein exposed prawns to FS compared to the control group,while no significant differences in the muscle were observedbetween groups (p<0.05). FS caused a significantincrease in the activity of antioxidant enzymes SOD,CAT, and GST compared to the control group (p<0.02).By contrast, LPO levels were not affected by the pesticide(p<0.05). These results indicate that P. argentinus is verysensitive to organophosphorus which alter biochemicalparameters that are related to antioxidant status. Thus,these parameters could be used as biomarkers forassessing water pollution.